Simple GFAAS Method for Determination of Pb, As, and Cd in Cannabidiol Extracts Used for Therapeutic Purposes - Nascimento, Patricia A.; Schultz, Juliana; Gonzalez, Mario H. [UNESP]; Oliveira, Andrea (Soc Brasileira Quimica, 2020)
Cannabis sativa has many promising medicinal applications for the mitigation, or even cure, of chronic diseases. The high bioaccumulation potential of C. sativa enables its use for the phytoremediation and detoxification of soil, may increase the levels of inorganic elements in products such as cannabidiol (CBD) extracts being necessary the evaluation/monitoring of the level of inorganic components, mainly the toxic species in these formulations. An analytical method employing graphite furnace atomic absorption spectrometry (GFAAS) was developed for the quantification of Pb, As, and Cd in commercial CBD extracts and homemade samples. The alkaline solubilization was employed in agreement with the external analytical curve, in a robust method. The limits of quantification were 0.26 (Pb), 0.067 (As), and 0.011 mu g g(-1) (Cd), with satisfactory accuracy (80-120%) and relative standard deviation (RSE)) values < 7%. The CBD extracts presented levels of Pb. As and Cd below the maximum limits established by regulatory agencies.
Keywords: Cannabis saliva L.; medicinal plant; inorganic quantification; toxic elements; alkaline solubilization